Remittances, financial development and education in Latin America - RUBIO CAMPOS, Lesly Yohana (KDI School, 2015)
This thesis studies the relationship between remittances and education in the period of 2000-2013, and how financial development interacts to influence the impact of remittances. We aim to focus on the Latin American region and use a fixed effect regression model to test our hypothesis. We find that remittances have a positive correlation with education, and it may be enhanced by the financial development of every country. The result is consistent with previous research regarding the positive impact of remittances on education, economic growth and other investments. There has been previous empirical work that proves how financial development influences the impact of remittances in areas such as economic growth. But the present study is the first to inquire on the interaction of financial development on education.
Thesis(Master) --KDI School:Master of Public Policy,2015